SECOND EDITION OF THE INTERNATIONAL STRATIGRAPHIC GUIDE - Zhamoida A.I. (My University, 1996)
The second, modified and essentially supplemented edition of the International Stratigraphic Guide, which was published in 1994, is discussed with consideration of its peculiar features and differences from the first edition published in 1976, and also from the Russian stratigraphie code of 1992. Three essential features differentiate the second edition of the guide from the first one: (1) chapters dealing with stratigraphic unconformity-bounded and magnetostratigraphic units were first introduced; (2) unlayered intrusive and metamorphic geological bodies were included into lithostratigraphic units; and (3) a glossary of stratigraphic terms was added. The Guide, which resulted from the fruitful cooperation of the World geological community, is appraised at its true worth.